ST Segment myocardial infarction due to totally occluded unprotected left main coronary artery (TOULM): an insight from nationwide database. (3rd October 2022) - Arabi, A; Rafie, I; Arafa, S; Alqahtani, A; Altamimi, O; Abujalala, S; Hamid, T; Ali, M; Alkindi, F; Alkhani, M; Al-Hijji, M; Altamimi, H; et al.
Abstract: Objective: This study sought to describe the clinical profile, management and short-term outcomes of patients with ST elevation myocardial infraction (STEMI) due to totally occluded unprotected left main coronary artery (TOULM). Methods: This is a retrospective analysis of nationwide STEMI database of patients who underwent primary percutaneous intervention (PPCI). Patients with TOULM are defined as having 100% acute thrombotic occlusion of the left main artery or subtotal occlusion with no more than TIMI 1 flow. Results: Between January 2011 and February 2022, 7107 patients underwent Primary Percutaneous Intervention for STEMI. 35 cases (0.5%) of all STEMI were due to TOULM. The average age of patients with TOULM was 51±14 years, predominantly male (94%) and had no prior cardiac history (94%). 11 patients (31%) suffered cardiac arrest and 16 (45%) were on mechanical ventilation prior to arrival to cardiac catheterization laboratory. The right coronary artery was the dominant vessel in 29 (89%) patients. Right to left collaterals were present in 15 (42%), absent in 8 (23%) and unknown (the right coronary artery was injected after TOULM intervention or not injected) in 12 (34%) patients. Mechanical circulatory support was used in 37% of the cases (IABP 8, ECMO 3 and ECMO plus IABP 2). Revascularization was achieved with PCI and stenting in 30 patients (86%). Five patients underwent urgent CABG after balloon angioplasty. Survival to hospital discharge was 55%. Conclusions: STEMI due to TOULM is a rare occurrence and involved mainly male with no prior cardiac history. Despite all the patients in our series undergoing revascularization, the in-hospital mortality is almost 50%. One major limitations of our study is we had no post-mortem data of any patient who died prior to coronary angiography, which potentially will lead to higher recorded cases of TOULM related mortality. Funding Acknowledgement: Type of funding sources: None.